Highly Potent 1H-1,2,3-Triazole-Tethered Isatin-Metronidazole Conjugates Against Anaerobic Foodborne, Waterborne, and Sexually-Transmitted Protozoal Parasites - Kumar, Sumit; Bains, Trpta; Won Kim, Ashley Sae; Tam, Christina; Kim, Jong; Cheng, Luisa W.; Land, Kirkwood M.; Debnath, Anjan; Kumar, Vipan (Frontiers in Cellular and Infection Microbiology, 2018)
Parasitic infections like amebiasis, trichomoniasis, and giardiasis are major health threats in tropical and subtropical regions of the world. Metronidazole (MTZ) is the current drug of choice for amebiasis, giardiasis, and trichomoniasis but it has several adverse effects and potential resistance is a concern. In order to develop alternative antimicrobials, a library of 1H-1,2,3-triazole-tethered metronidazole-isatin conjugates was synthesized using Huisgen's azide-alkyne cycloaddition reaction and evaluated for their amebicidal, anti-trichomonal, and anti-giardial potential. Most of the synthesized conjugates exhibited activities against Trichomonas vaginalis, Tritrichomonas foetus, Entamoeba histolytica, and Giardia lamblia. While activities against T. vaginalis and T. foetus were comparable to that of the standard drug MTZ, better activities were observed against E. histolytica and G. lamblia. Conjugates 9d and 10a were found to be 2–3-folds more potent than MTZ against E. histolytica and 8–16-folds more potent than MTZ against G. lamblia. Further analysis of these compounds on fungi and bacteria did not show inhibitory activity, demonstrating their specific anti-protozoal properties.